Date rape - Thomas, Erin; Wilson, Nancy Rabuck; Educational Video Network (United States: Educational Video Network, 2001)
Total strangers, but rather by people who are known to the victims, do not commit most rapes. Date rape is a violation of a woman's body that's exacerbated by a violation of her trust. This programmed explains how a failure to communicate effectively is at the heart of many date rape situations.
Executive producer, George H. Russell
Narrator: Jude L. Routh
Keywords: Rape; Date rape